Implementation of recycled products at Public universities in Malaysia / Nor Syafika Ibrahim and Tajudin Saidin - Ibrahim, Nor Syafika; Saidin, Tajudin (2020)
Raw materials are an important aspect of any business, particularly those that carry out manufacturing and construction activities. There are now recycled alternatives to many products and resources. These could help to cut costs and reduce your impact on the environment. Creating goods and services from recycled materials could also enable to market of the products as having less impact on the environment. Waste management has to be a crucial aspect related to the economic status of a country and the lifestyle of its population. Others, Malaysia having problems with less utilization of recycled products and this issue must be highlighted this time. Recycling in Malaysia involves the purposes of energy saving. With the growing energy demand and to conserve energy in an era of unpredictable energy markets, recycling is an indispensable option. The objectives were (1) to determine the current utilization practice of recycled products in the public university, (2) to identify the weakness of utilizing recycled products in a public university in Malaysia, and (3) to improve the utilization of the recycled products towards the public university building. The main purpose of this research is to improve the utilization of recycling materials in the construction industry in Malaysia. To achieve the best finding, the questionnaire was distributed to students of public higher institutions in peninsular Malaysia. A total of 145 respondents were involved in the questionnaire survey and analysed using descriptive analysis. The results presented show that the current practice utilization in this country still at a low level and besides that result, it shows there are also weaknesses in utilizing the recycled product. However, it is found that the solution in improving the utilization of recycled product gives the most effective strategy to minimize waste. By doing this research, it can be concluded that recycling plays an important role to practice every single person in enhancing their interest to keep the environment safe and sustainable.